The Criminal Selfie: conveying Grievance While Recording and Live Streaming Antisocial Behavior - Sandhu, Ajay (European journal on criminal policy and research, 2023)
Despite attempts to regulate content, social media platforms continue to host images of antisocial behavior and crime. These images include dashboard videos of road rage and CCTV footage of shoplifting, as well as more extreme recordings of torture, sexual assault, suicide, and mass shootings. These images are often produced by offenders of their own volition using smartphone cameras and wearable recording devices. We understand criminal selfies as media content of antisocial behavior or crime produced by or with the awareness of an offender. By producing a criminal selfie, an offender renders themselves vulnerable to public scrutiny, legal punishment, and other negative outcomes. Yet criminal selfies remain a popular form of toxic online communication. This manuscript theorizes that one of the previously underappreciated explanations for criminal selfies is a desire to broadcast personal grievances. In such cases, they allow an offender to publicize their motivating politics and to offer them to an online audience for consideration and discussion. Antisocial content often evokes an unfavorable ratio of denunciation versus supportive responses. We claim that some offenders wager that a criminal selfie nonetheless earns their grievances a degree of awareness and, potentially, consequence. Some criminal selfies reflect a willingness to self-incriminate by documenting antisocial behavior in hopes that their images will contribute to public discourse. This article contributes to studies of criminal visibility by addressing how it can be intended as political expression. We first outline the concept of the criminal selfie and how it reflects a changing relationship between visibility and criminality in contemporary digital society. We then review literature on the motives of criminals who film themselves. We seek to compliment this literature by considering socially and politically aggrieved individuals producing antisocial content. This includes livestreams of white nationalist mass shootings (Christchurch, Halle) as well as a series of Reddit groups that solicit and (counter-)denounce antisocial grievances by digital media users (r/iamverybadass, r/publicfreakout, r/iamatotalpieceofshit).